UN Development Goals: Sustaining the Southeast Asian Fisherman - Serina Rahman (2015)
The UN Sustainable Development Goals highlight the need to protect the oceans, coastlines and small-scale fishermen. However, this may be in conflict with ASEAN’s bid to reach the targets set out in the ASEAN Economic Community Blueprint. Serious political will and effective on-the-ground effort will be vital in preserving Southeast Asia’s highly endangered fishing heritage.